Natural variation at XND1 impacts root hydraulics and trade-off for stress responses in Arabidopsis - Ning Tang (Nature Portfolio, 2018)
Soil water uptake is a major determinant of plant performance and stress tolerance. Here the authors show that, by affecting xylem formation in the root, natural variation at the Arabidopsis XND1 locus has contrasting effects on root hydraulics and drought tolerance versus pathogen resistance.